Electromyographic analysis of the flip turn technique - Pereira, S. M.; Vilar, S.; Gonçalves, P.; Fernandes, S.; Fernandes, R.; Roesler, H.; Vilas-Boas, J. P. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to assess the electric potential of the muscles vastus lateralis (VA), gastrocnemius (GM), tibialis anterior (TA) and biceps femoris (BF) during the front crawl flip turn technique. The subject was an elite male front crawl/backstroke swimmer. Surface active electrodes were used and EMG signals were transmitted by 25m long cables to the main amplifier. BF and TA showed higher participation in the beginning of the "rotation", implying that its action is fundamental to a higher rotation velocity. In the "wall contact", TA and GM muscles seemed to be in co-activation. VL presented a significant activation during the "impulse". In the beginning of the "gliding", all the studied muscles presented low EMG signals. These new methodology procedures seem to be valid and reliable to assess the muscular function during the flip turn.